18F-DOPA uptake illustration acts as an indicator for renal sympathetic activity - Wu, Rui; Shi, Saijian; Huang, Yuanjie; Tian, Feng; Hou, Jiqin; Kong, Xiangqing; Sheng, Longxiang; Zhang, Tao; Tang, Lijun; Sun, Wei (Frontiers in Physiology, 2025)
Renal denervation (RDN) has emerged as a promising therapeutic approach for hypertension, particularly in patients with refractory hypertension. However, non-invasive measurement of the degree of renal nerve ablation has still been a challenge. This study aims to develop a novel method for assessing the efficacy of RDN. Based on 18F-DOPA micro PET-CT imaging, we demonstrate that bilateral RDN significantly reduces 18F-DOPA uptake in the kidneys of spontaneously hypertensive rats (SHRs) with normal renal function. A similar trend was observed in Wistar Kyoto rats (WKYs). Meanwhile, the effectiveness of RDN was further validated through blood pressure (BP) monitoring, Western blot analysis of sympathetic nerve markers, and immunohistochemistry of nerves. In conclusion, our data suggest that 18F-DOPA PET-CT imaging is parallel with the sympathetic nerve activity of kidney which provides valuable insights for in vivo evaluating the efficacy of RDN and may serve as a critical tool for clinically assessing its therapeutic outcomes. The underlying molecular mechanisms responsible for the observed reduction in renal 18F-DOPA uptake in SHRs following RDN warrant further investigation.